Rates of gypsum and development of soybean in clay red Latossol in the cerrado region - Kaneko, Flavio Hiroshi; Arf, Marcelo Valentini; Dal Bem, Edjair Algusto; Buzetti, Salatier [UNESP]; Freitas Leal, Aguinaldo Jose; Gitti, Douglas de Castilho (Univ Fed Grande Dourados, 2015)
Many questions about the benefits and harms of gypsum are verified in the field by technicians and farmers, mainly in relation to the highest rate of gypsum without loss to crop yield Aiming to determine the highest rate of gypsum, that did not cause damage on soybean yield, was conducted a work with rates of gypsum: 0; 1,400; 2,800; 5,600 and 11,200 kg ha(-1) in Chapadao do Sul-MS in 2010/2011 and 2011/2012 crops. The experimental design was a randomized block with 5 replications. Based on the results obtained it was found that application of gypsum did not affect grain yield of soybean in both years, indicating that the official recommendation of gypsum, suggested by Souza & Lobato (2004) can be safely used by technicians and soybean producers in the region of savannah.
Keywords: gypsum; no tillage; soil correction